Comparative life cycle assessment of pelletized biomass fuels from corncobs and rubberwood sawdust - Phrommarat, Bhanupong; Arromdee, Porametr (International Journal of Renewable Energy Development, 2025)
This study investigates and compares the environmental impacts of pelletized biomass fuel production from corn cobs and rubberwood sawdust using the Life Cycle Assessment (LCA) methodology across the entire cradle-to-grave process. The assessment encompasses raw material acquisition, production, industrial use, and transportation. Data were collected on resource usage, energy consumption, water usage, and greenhouse gas (GHG) emissions, with the functional unit set as 1 ton of steam generated by a steam generator. Environmental impacts were evaluated using the CML (baseline) 2015 method in openLCA software, with data drawn from the Ecoinvent 3.4 database. Comparisons with other biomass types were also included. The findings indicate that corn cobs are a preferable raw material for pelletized biomass production compared to rubberwood sawdust, as they require less electricity and fewer resources across the lifecycle due to a simpler production process. The study reveals that the highest environmental impacts occur during biomass pellet production, particularly in rubberwood processing, which is energy intensive. Climate change impacts are most significant in the steam production stage, attributed to GHG emissions from biomass pellet combustion. Furthermore, fossil fuels used in other processes and transportation contribute to the overall environmental footprint. Mitigating these impacts would benefit from enhancing energy efficiency, reducing GHG emissions, and expanding the use of renewable energy in production processes. These measures could substantially lessen the environmental effects associated with pelletized biomass fuel production. The impact of data uncertainties in steam production from biomass pellets was assessed through sensitivity analysis. Four key parameters were identified as having significant variability, including transportation of pellets from production plants to steam plants, corn kernel selling price, natural rubber selling price, and allocation method. The transportation distance and agricultural product prices (corn kernel and natural rubber) introduce minimal uncertainty into the LCA results within the tested range (±10%).